GAMIFICATION IN MANAGEMENT EDUCATION - Teresa PIECUCH; Jolanta STEC-RUSIECKA; Agata WARMIŃSKA; Bożydar ZIÓŁKOWSKI; Anna MOLTER; Artur KARWATKA; Olga BUCKIŪNIENĖ (Humanities and Social Sciences, 2023)
Gamification, which uses the mechanisms of games to acquire knowledge and various types of skills to build people’s involvement in a specific activity, is playing an increasingly important role. This study aims to emphasize the importance of gamification in the management process, with particular attention to its use in the educational process. It employs a critical literature review, observation, and case studies, containing an analysis of active gamification-based methods used in teaching management (organization and management) and production management. On the basis of the pilot program MANAGER BOB IN, the game used during the production management course, and the experiences of the authors of the study in creating various games, it can be concluded that it is necessary to allocate more time during organizational classes to explain the principles and benefits of participation in gamification, and to extend the time for the implementation of selected challenges. Information feedback is also important, as is the use of various technical solutions that affect the attractiveness of games and the entire educational process.